Genetic variation in thrombin-activatable fibrinolysis inhibitor (TAFI) is associated with the risk of splanchnic vein thrombosis - de Bruijne, Emile L. E.; Murad, Sarwa Darwish; de Maat, Moniek P. M.; Tanck, Michael W. T.; Haagsma, Elizabeth B.; van Hoek, Bart; Rosendaal, Frits R.; Janssen, Harry L. A.; Leebeek, Frank W. G.; for the Liver and Thrombosis Study Group (Thrombosis and Haemostasis, 2007)
Splanchnic vein thrombosis (SVT) has been associated with a hypercoagulable state. Thrombin-activatable fibrinolysis inhibitor (TAFI) may contribute to a hypercoagulable state, and therefore we were interested in the role of TAFI in SVT. Since the disease is frequently associated with liver insufficiency, which affects plasma levels ofTAFI, we studied the role of variation in theTAFI gene in SVT. In a multicenter case-control study on 118 patients with SVT (39 Budd-Chiari syndrome and 85 portal vein thrombosis) and 118 population-based controls, the relationship of SVT with single nucleotide polymorphisms (SNPs) and haplotypes in the TAFI gene (- 438G/A, Ala147Thr, Thr325Ile and 1583A/T) was determined. The risk for SVT was decreased (OR 0.2,95% CI 0.1–0.7) in 147Thr/Thr homozygotes and slightly,but not significantly,increased in carriers of the 325Ile allele (OR 1.6, 95%CI 0.9–2.7). Haplotype analysis confirmed that the Ala147Thr SNP has the strongest association with risk of SVT. In conclusion, genetic variation in the TAFI gene is associated with risk of SVT, suggesting a role for TAFI in the pathogenetic mechanism of SVT.
Keywords: Thrombin-activatable fibrinolysis inhibitor; Budd-Chiari syndrome; portal vein thrombosis; single nucleotide polymorphism; splanchnic vein thrombosis; inflammation; fibrinolysis